Strategi Manajemen Hubungan Sekolah dan Masyarakat dalam Pengembangan Citra Positif untuk Preferensi Konsumen Pendidikan (Studi Kasus SD My Little Island Malang) - Rahmat, Salwa Hanifa; Timan, Agus; Supriyanto, Achmad (Proceedings Series of Educational Studies, 2025)
This research examines school and community relationship management strategies in developing a positive image at My Little Island Malang Elementary School, with a focus on public relations strategies, public relations activities to build a positive image, and educational consumer preferences. SD My Little Island Malang implements effective public relations strategies through superior programs such as Character Solution International (CSI) which emphasizes student character development. The use of technology, such as websites and social media, supports transparency and easy access to information, which in turn increases parental trust and preference for schools. This research uses qualitative methods with NVivo data analysis through interviews, observation and documentation. The research results show that good public relations management has a positive effect on education consumer preferences, with school policies that promote tolerance between religions and cultures increasing the school's attractiveness in the eyes of a multicultural society. Based on the results of the analysis, it is recommended that school principals support improving digital infrastructure for the public relations and IT teams, strengthen interactive activities with the community and parents, and develop the school website to be more interactive and responsive. Parents are also expected to participate more actively in their children's learning and collaborate with schools, and further research can use these findings as guidelines in developing successful public relations management strategies in educational institutions.